Antiproliferative Potency of God’s Crown Fruit (Phaleria macrocarpa) Extract Against Breast Cancer Cell - Hasim Hasim; Yonathan Arderian Mantik; Husnawati Husnawati; Bambang Pontjo Priosoeryanto; Ratna Puspita (Borneo Journal of Pharmacy, 2022)
Breast cancer is a sickness caused by abnormal cell growth in the breast. Mahkota Dewa fruit or god’s crown fruit products (Phaleria macrocarpa) contain flavonoids, alkaloids, polyphenols, and tannins associated with active compounds. This work directs to influence the potency of P. macrocarpa fruit as an antiproliferative agent against breast cancer cells (MCF-7 cells). The antiproliferative potency of P. macrocarpa fruit was proved by extracting and fractionating P. macrocarpa fruit using maceration. The cytotoxicity of extracts and fractions was determined using Brine Shrimp Lethality Test (BSLT). The antiproliferative potency against MCF-7 cells was tested using the hemacytometer approach. This work demonstrates the crude ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction. The LC50 values in crude ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction were 13.72 ppm, 147.55 ppm, 405.81 ppm, and 149. 07 ppm severally. Phaleria macrocarpa fruit has shown antiproliferation potency against MCF-7 cells. The maximum part of crude ethanol extract antiproliferative potency (56 ppm) effectively suppressed MCF-7 cell growth by 70. 9% while doxorubicin (100 ppm) by 46. 92%. This work confirms that crude ethanol extract of P. macrocarpa fruit interacts synergistically as an antiproliferative compound against MCF-7 cells.